Paediatric cause of back pain in young adult. A case report - Sharifudin, Mohd Ariff; Johari, Joehaimey; Omar, Ahmad Sabri (2011)
Eosinophilic granuloma is a non-neoplastic lesion commonly occurs in paediatric age group, arising from clonal proliferation of Langerhans-type histiocytes. Vertebral involvement has been frequently reported in approximately 10-15% of cases, but involvement of the spinal cord and roots remains a rare occurrence. Patients may present with progressive back pain, with or without neurologic symptoms. We describe an additional case of Langerhans cell histiocytosis (LCH) of the spine in a young adult presented with a progressive back pain with quadriparesis.